A Novel Reliability Assurance Method for Cyberphysical System Components Substitution. (19th November 2012) - Wang, Peng; Xiang, Yang; Zhang, Shaohua
Abstract : Reliability of cyberphysical system (CPS) components substitution is an important issue for CPS troubleshooting and system upgrading. In this paper, decision problem of components substitution is regarded as decision problem of services substitution through a service-oriented architecture of CPS. Further, a reliability assurance method for CPS service substitution is proposed, which comprises two parts. The first one is a qualitative judgment method for CPS service substitution according to the relationship between service compatibility and substitution based on time-space π -calculus with time and space operators. The other one is consisted of substitution processes from above judgment results based on service management theory. Finally, a case study is performed to show how to apply this method to ensure CPS components reliable substitution. The experimental result shows that this method is reasonable and feasible.